Barriers and Facilitators That Influence Social Participation in Older Adults With Dual Sensory Impairment - Jaiswal, Atul; Fraser, Sarah; Wittich, Walter (Frontiers in Education, 2020)
Introduction: The proportion of older adults with combined acquired vision and hearing impairments (referred to as Dual Sensory Impairment/DSI) is growing, and their unique care needs are beginning to receive increased attention. Considering the age-related demographic shift, one million older adults in Canada are expected to experience DSI by 2036, and evidence suggests that DSI is associated with communication difficulties, cognitive decline, depression, functional decline, and participation challenges. Given that the goal of sensory rehabilitation is to improve participation, the study explored perceived contextual barriers and facilitators of social participation among older adults with DSI to better understand their lived experience. Methods: The International Classification of Functioning, Disability and Health (ICF) was used as a framework to identify and describe the contextual factors (environmental and personal) that influence the social participation of older adults with DSI. Sixteen older adults with DSI (mean age = 86 years, SD = 7; 9 female; registered with an urban sensory rehabilitation organization) were interviewed using a semi-structured qualitative interview guide. Interviews were audio-recorded, transcribed, and then analyzed using a content analysis approach. Results: Environmental factors, such as societal attitudes towards disability, access to technology aids, and availability of transportation services emerged as the most important factors influencing participation. The onset and type of the impairments and attitude towards one’s disability were important personal factors affecting the participation. The availability of social support and the use of assistive devices (e.g., magnifiers, glasses, and hearing aids) were reported to be facilitators. In contrast, the inaccessibility of the built environment and the cost and limited availability of accessible transportation were key barriers to their social participation. Discussion: Our study indicated that assistive devices facilitate older adults with DSI in their day-to-day functioning and improve social participation, while expensive and inadequate transportation services may deter their participation. For rehabilitation professionals working with older adults with DSI, it is crucial to consider the barriers to and facilitators of social participation when designing interventions. Future research is warranted to investigate the role of assistive devices and transportation in improving the social participation of older adults with DSI.